Loss aversion and labor supply - Lorenz Goette; David Huffman; Ernst Fehr (Institute for the Study of Labor (IZA), 2003)
In many occupations workers? labor supply choices are constrained by institutional rules regulating labor time and effort provision. This renders explicit tests of the neoclassical theory of labor supply difficult. Here we present evidence from studies examining labor supply responses in ?neoclassical environments? in which workers are free to choose when and how much to work. Despite the favorable environment the results cast doubt on the neoclassical model. They are, however, consistent with a model of reference dependent preferences exhibiting loss aversion and diminishing sensitivity.
Keywords: B49; J22; 330; labor supply; intertemporal substitution; loss aversion; reference dependent; Arbeitsangebot; Arbeitszeit; Zeitpräferenz; Risikoaversion; Prospect Theory; Theorie; Deutschland